2014
DOI: 10.1016/j.midw.2013.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The role of religion in decision-making on antenatal screening of congenital anomalies: A qualitative study amongst Muslim Turkish origin immigrants

Abstract: counsellors should be aware of the role of religious beliefs in the decision-making process on antenatal screening tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 17 publications
2
40
0
Order By: Relevance
“…Religious women, for example, are more likely to accept a child with Down syndrome and less likely to terminate their pregnancy [30]. As in previous studies, we found a strong association between religious background and declining the CT [1018]. An additional finding in our study is that the influence of religious background is faith-specific.…”
Section: Discussionsupporting
confidence: 85%
“…Religious women, for example, are more likely to accept a child with Down syndrome and less likely to terminate their pregnancy [30]. As in previous studies, we found a strong association between religious background and declining the CT [1018]. An additional finding in our study is that the influence of religious background is faith-specific.…”
Section: Discussionsupporting
confidence: 85%
“…This means that, for a Muslim woman living in the Netherlands who is guided by her religious beliefs regarding the moment of ensoulment (120 days after conception) information indicating a serious anomaly resulting from routine second-trimester ultrasound screening will be received too late to inform her choice regarding continuation of the pregnancy. Similarly, previous studies showed that not all pregnant Muslim women themselves have sufficient knowledge of the rulings of their own specific tradition on termination in the case of a congenital anomaly [18,35]. Neter et al observed similar findings and argued that midwives, in their role as counselors, are expected to inform Muslim women about prenatal screening tests and to discuss the possibility of termination if it comes to a fetus with serious anomalies [37].…”
Section: Discussionmentioning
confidence: 84%
“…The MIMES model identified a number of factors that are relevant in test uptake decisions, including not only well-known factors such as age, parity, family life and personal experience, but also ‘identity markers’ such as ethnicity and religion [10-14]. It is acknowledged that the difficult questions that confront clients in decision-making may be influenced by their religious convictions [15-18]. As the shared decision-making approach prescribes taking the client’s perspective into account, the question arises as to whether asking about client’s religious convictions should also be part of the counseling process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations